PENGARUH CAPITAL ADEQUACY RATIO (CAR), BIAYA OPERASIONAL PENDAPATAN OPERASIONAL (BOPO), NON PERFORMING LOAN(NPL), NET INTEREST MARGIN (NIM) DAN LOAN TO DEPOSIT RATIO (LDR) TERHADAP RETURN ON ASSET (ROA) BANK SULTRA - Ainul Hasyim; Ibnu Hajar; La Utu; Sujono Sujono (Pascasarjana Universitas Halu Oleo, 2017)
Ainul Hasyim (G2 D1 15105). Influence of Capital Adequacy Ratio (CAR), Operational Income Operating Expense (BOPO), Non Performing Loan (NPL), Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) on Return on Asset (ROA ) Bank Sultra. Guided by: 1) Ibn Hajar, 2) La Utu.This study aims to examine and analyze the effects of simultaneous and partial Capital Adequacy Ratio (CAR), Operational Income Operating Cost (BOPO), Net Performing Loan (NPL), Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) Against Return On Asset (ROA) of Bank Sultra.This research data is quarterly report of Bank Sultra period 2006 - 2015 which amounted to 39 sample. The data in the study were analyzed by using multiple regression with SPSS ver. 20 software.Result of research: 1) simultaneously Capital Adequacy Ratio (CAR), Operational Operating Income (BOPO), Net Performing Loan (NPL), Net Interest Margin (NIM) and Loan to Deposit Ratio (LDR) have significant effect on ROA, 2) Capital Adequacy Ratio (CAR) has a significant positive effect on ROA, 3) Operational Cost of Operating Income (BOPO) has significant negative effect to ROA, 4) Net Performing Loan (NPL) has positive but not significant effect on ROA, 5) Net Interest Margin ) Have no significant positive effect on ROA, 6) Loan to Deposit Ratio (LDR) has negative but not significant effect on ROA.